Automated Pipeline for Regional Epicardial Adipose Tissue Distribution Analysis in the Left Atrium - Lluch, Èric; Castañeda, Eduardo; Weiss, Maximilian E.R.; Vizitiu, Anamaria; Jacob, Athira; Jami, Jitin; Audigier, Chloé; Meister, Felix; Mihalef, Viorel; Passerini, Tiziano (Lecture Notes in Computer Science, 2025)
Atrial fibrillation (AF) is the most common cardiac arrhythmia, affecting approximately 3% of the global population and rising to 11% in individuals over 80 years old. The distribution of epicardial adipose tissue (EAT) around the atria plays a significant role in the pathophysiology of AF, yet its regional analysis remains underexplored. This paper introduces an automated pipeline capable of segmenting 14 atrial regions from patient CT angiograms, a notable advancement over previous attempts to automate the creation of synthetic anatomical or physics-based twins. Our fully automatic pipeline requires no human supervision and provides the regional EAT quantification successfully on 91.9% of the analyzed patients for which the LA and its structures were automatically segmented (1797 out of 1954 patients), including the automatic segmentation of the aorta and pericardium to assess EAT volume around the left atrium. By applying principal component analysis of the regional EAT to analyze a separate dataset of 84 individuals who were clinically labeled, we identified a distinct group that contained all the patients with AF. This finding suggests that there is a significant link between the pattern of fat distribution and AF. This novel approach has the potential to enhance our understanding of AF and improve patient outcomes by enabling large-scale, regional fat analysis in an automated manner on all patients with accurate segmentation of left atrial structures.
CRIS-Team Scopus Importer:2025-05-16
Keywords: atrial fibrillation; automatic pipeline; Epicardial adipose tissue